A review of thin film electrolytes fabricated by physical vapor deposition for solid oxide fuel cells. (29th October 2022) - Liang, Fuyuan; Yang, JiaRan; Zhao, Yuanyuan; Zhou, Yexin; Yan, Zilin; He, JianChao; Yuan, Qunhui; Wu, Junwei; Liu, Peng; Zhong, Zheng; Han, Minfang
Abstract: The ohmic resistance in solid oxide fuel cells (SOFCs) mainly comes from the electrolyte, which can be reduced by developing novel electrolyte materials with higher ionic conductivity and/or fabricating thin-film electrolytes. Among various kinds of thin-film fabrication technology, the physical vapor deposition (PVD) method can reduce the electrolyte thickness to a few micrometers and mitigate the issues associated with high-temperature sintering, which is necessary for wet ceramic methods. This review summarizes recent development progress in thin-film electrolytes fabricated by the PVD method, especially pulsed laser deposition (PLD) and magnetron sputtering. At first, the importance of the substrate surface morphology for the quality of the film is emphasized. After that, the fabrication of thin-film doped-zirconia and doped-ceria electrolytes is presented, then we provide a brief summary of the works on other types of electrolytes prepared by PVD. Finally, we have come to the summary and made perspectives. Graphical abstract: Electrolytes strategy for lowering the operating temperature. Image 1 Highlights: The application of physical vapor deposition in the preparation of SOFCs electrolytes is summarized systematically. The effects of deposition process and film configuration on thin-film electrolytes are carefully discussed. The challenges and prospects of thin-film electrolytes fabricated by physical vapor deposition are pointed out.